EDUCATION MANAGEMENT IN A PUBLIC UNIVERSITY UNDER THE FRAMEWORK OF AN ACADEMIC AUDITING - Morales Calle, Luz (2015)
The current problems of educational management in the Faculty of Management of a public university in the framework of academic auditing, promotes re-search of qualitative approach and descriptive whose study sample was 39 teachers and 305 students from the Economics Sciences Faculty , Management and Accounting of the National University San Cristobal de Huamanga, where two instruments were used: first, a survey on academic audit consists of 18 items and three dimensions- an evaluation of the academic situation, OCI control actions and lack of an academic auditing- and second to measure the administrative management variable consisting of 35 items corres-ponding to three dimensions -administrative mana-gement, academic management and deficiencies in the academic area. It was found that the absence of an evaluation of the academic situation affects negatively on the educa-tional management, the weaknesses in the education management systems are due to the lack of quality systems, academic audit processes; the actions of OCI contribute little to educational management, by not implementing an academic auditing. Finally, deficiencies in the academic area are because of lack of policies, quality assurance systems and processes for decisions making on improving the academic quality; concluding that the design and implementation of an academic audit can significantly improve the educa-tional management of the Faculty of Administrative Sciences in a public university.